Comprehensive Teacher Induction - Britton, E.D. author. aut Link
XIV, 404 p.
Keywords: This book provides a detailed examination of how systems located within five countries shape the early career learning of beginning teachers. It describes, discusses and analyzes comprehensive teacher induction found within France, Japan, New Zealand, Shanghai and Switzerland. We refer to the phenomena we observed as induction ‘systems’ because they are am- tious, substantial and established: all beginning teachers in these various locales are served; there are no unfunded mandates; these systems have been in place for 10–25 years. Nevertheless, they are still evolving, und- going review and change – they are dynamic systems. While sharing such similarities, these systems also present striking contrasts in their purposes, policies, program design and the specific activities that constitute them. These induction systems operate within countries having both centr- ized and decentralized education systems, and within large jurisdictions as well as smaller ones. Although we primarily looked at beginning mathe- tics and science teachers of the lower secondary grades, many aspects are relevant to novice teachers of all school subjects at these grade levels, and some structures and insights are germane to the induction of elementary teachers as well.